2010
DOI: 10.1007/s12539-010-0093-y
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of quantum tunnelling in enzyme-catalysed hydrogen transfer reactions

Abstract: Transfer of hydrogen as a proton, hydride or hydrogen atom is an important step in many enzymic reactions. Experiments show kinetic isotope effects (KIEs) for some enzyme-catalysed hydrogen transfer reactions that deviate significantly from the limits imposed by considering the differences in mass of the isotopes alone (i.e. the semiclassical limit). These KIEs can be explained if the transfer of the hydrogen species occurs via a quantum mechanical tunnelling mechanism. The unusual temperature dependence of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 147 publications
0
16
0
1
Order By: Relevance
“…Although this apparent KIE must not necessarily reflect the true intrinsic KIE, the magnitude is considerably higher than expected for a semiclassical mechanism. [16] One has to bear in mind, however, that the observed KIE results from a combination of several KIEs in different transition states with individual kinetic significances for overall catalysis including several primary (hydrogen abstraction of C8 and subsequent recombination with the peroxyl radical) and a-secondary effects (hydrogen abstraction from C8). Despite a potential combination of KIEs from different transition states, an apparent deuterium KIE of over 30 is usually indicative of hydrogen-tunneling contributions.…”
Section: Deuterium Kinetic Isotope Effect Studies Under Multiple Turnmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this apparent KIE must not necessarily reflect the true intrinsic KIE, the magnitude is considerably higher than expected for a semiclassical mechanism. [16] One has to bear in mind, however, that the observed KIE results from a combination of several KIEs in different transition states with individual kinetic significances for overall catalysis including several primary (hydrogen abstraction of C8 and subsequent recombination with the peroxyl radical) and a-secondary effects (hydrogen abstraction from C8). Despite a potential combination of KIEs from different transition states, an apparent deuterium KIE of over 30 is usually indicative of hydrogen-tunneling contributions.…”
Section: Deuterium Kinetic Isotope Effect Studies Under Multiple Turnmentioning
confidence: 99%
“…Despite a potential combination of KIEs from different transition states, an apparent deuterium KIE of over 30 is usually indicative of hydrogen-tunneling contributions. [16] Future studies, including a rigorous analysis of the temperature dependence of the apparent KIEs will be carried out to further dissect the molecular mechanism of hydrogen transfer from C8 to the tyrosyl radical. In contrast, dideuteration at C5 has only a marginal influence on the macroscopic kinetic constants of PpoA, as a matter of fact, the effect on V/K is more pronounced than on V. The small deuterium KIE in case of [D 2 ]C5-OA suggests that rearrangement of 8-HPOME at the P450 domain of the enzyme has a little kinetic significance; for example, it is not rate-determining for the overall catalysis.…”
Section: Deuterium Kinetic Isotope Effect Studies Under Multiple Turnmentioning
confidence: 99%
“…The unusually high KIE is likely due to the tunnelling mechanism of the proton transfer. [58,61] A QT study of this process, reported in Ref. [56] …”
Section: Example: a Qt Simulation Of The Proton Transfer In Slo-1mentioning
confidence: 99%
“…[10] In addition, for both enzymes, high-resolution crystal structures are available. [53] Both MADH and AADH share an a 2 b 2 hetero-tetrameric structure consisting of two heavy a-subunits and two light bsubunits.T he b-subunits display significant sequence identity and are responsible for the catalytic activity. [52] With high-resolution crystal structures and kinetic datar eadily available, AADH and MADH have been important realistic models for investigating theoretical tunneling processes in enzymes.…”
Section: Introductionmentioning
confidence: 99%